Pelatihan Pembuatan Toko Online Berbasis Marketplace untuk Pemberdayaan Ibu Rumah Tangga - Khaerul Anam; Martanto; Azzahra Moudy Fajria; Bagus Hermawan (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community service program aims to empower housewives through the creation and management of online stores based on marketplaces. This activity is motivated by the great potential of e-commerce in providing time flexibility and additional economic opportunities for housewives. The implementation method includes intensive training on online store creation, product management, digital marketing, and customer service. As a result, participants are able to create their own online stores and manage their operations well. This program provides a practical solution for housewives to increase income and economic independence. Further assistance and program expansion are recommended to reach more participants.